2021
DOI: 10.34172/ps.2021.13
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vitamin D supplementation on mortality rate and clinical outcomes of COVID-19 patients: A systematic review and meta-analysis

Abstract: Background: Several studies have suggested the positive impact of vitamin D on patients infected with SARS-CoV-2. This systematic review aims to evaluate the effects of vitamin D supplementation on clinical outcomes and mortality rate of COVID-19 patients. Methods: A comprehensive search was conducted through the databases of PubMed, Scopus, Web of Knowledge, Embase, Ovid, and The Cochrane Library without time and language limitation, until December 16, 2020. The results were screened, and the outcomes of inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
1
27
1
Order By: Relevance
“…Four other systematic‐reviews and meta‐analyses on the effect of vitamin D supplementation on mortality and ICU admissions of COVID‐19 patients were retrieved from database searching. 45 , 46 The first one, 45 that included 532 COVID‐19 patients from three studies, concluded that vitamin D supplementation was associated with significant lower rates of ICU admission ( p < 0.0001), while no significant benefit for mortality was observed; these findings are similar to the results of our study. However, compared to that study, our meta‐analysis includes a larger number of patients because at the time we performed our search more studies had been published.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Four other systematic‐reviews and meta‐analyses on the effect of vitamin D supplementation on mortality and ICU admissions of COVID‐19 patients were retrieved from database searching. 45 , 46 The first one, 45 that included 532 COVID‐19 patients from three studies, concluded that vitamin D supplementation was associated with significant lower rates of ICU admission ( p < 0.0001), while no significant benefit for mortality was observed; these findings are similar to the results of our study. However, compared to that study, our meta‐analysis includes a larger number of patients because at the time we performed our search more studies had been published.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, as previously explained, we decided a priori to use the random‐effects model, which we believe to be more appropriate for this meta‐analysis due to different designs of the included studies, while in the aforementioned study the significant result was obtained with the application of fixed effect model. The second meta‐analysis, which was obtained from a preprint server, 46 included only clinical trials, quasi experimental and pilot studies. Only one of the included studies reported on ICU admissions, while 3 studies that included a total of 190 patients reported on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study that used Mendelian randomization to assess the effect of increased vitamin D on COVID-19 outcomes also showed no significant difference in risk of hospitalization and did not support the use of vitamin D supplementation in the general population to prevent COVID-19 outcomes [ 36 ]. A few previous systematic literature reviews and meta-analyses have addressed the association between vitamin D status and COVID-19 related mortality and ICU admission rate and showed conflicting results [ 17 , 37 , 38 , 39 ]. With ten additional studies, our findings are in line with the 2021 meta-analysis of COVID-19 patients including 13 studies (10 observational with 3 RCTs), which concluded that vitamin D supplementation was significantly associated with a lower risk of ICU admission and mortality, with an effect size comparable to what we found in the present study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Martínez and colleagues 39 concluded that vitamin D could not decrease virus replication in both animal and clinical data. A recent systematic review and meta-analysis of four studies involving 259 patients 40 showed that vitamin D supplementation led to a statistically significant lower mortality rate in patients with COVID-19 (OR=0.264, 95% CI=0.099-0.708, p-value=0.008). Moreover, Rastogi et al 41 showed that vitamin D supplementation could significantly decrease serum levels of fibrinogen and inflammatory markers; however, no major difference was observed in the levels of procalcitonin, C-reactive protein, D-dimer, and ferritin.…”
Section: Fat-soluble Vitamins Vitamin D (Ergocalciferol-d2 Cholecalciferol-d3 Alfacalcidol)mentioning
confidence: 99%